MicroRNA-539-5p-Loaded PLGA Nanoparticles Grafted with iRGD as a Targeting Treatment for Choroidal Neovascularization - Jouri S. Alanazi; Fulwah Yahya Alqahtani; Fadilah Sfouq Aleanizy; Awwad A. Radwan; Ahmed Bari; Qamraa Hamad Alqahtani; Hosam Gharib Abdelhady; Ibrahim Alsarra (MDPI AG, 2022)
Choroidal neovascularization (CNV) is a major cause of visual impairment that results from excessive growth of blood vessels in the eye's choroid. The limited clinical efficacy of the current therapy for this condition requires the emergence of new treatment modalities such as microRNA (miRNAs). A recent study identified microRNA-539-5p (miR-539) as an angiogenic suppressor in a CNV animal model; however, its therapeutic delivery is limited. Therefore, this study aims to formulate miR-539 in targeted nanoparticles (NPs) prepared from polylactic-co-glycolic acid (PLGA). The NPs were decorated with internalizing arginylglycylaspartic (RGD) peptide (iRGD), which specifically targets the alpha-v-beta-3 (αvβ3) integrin receptor that is overexpressed in blood vessels of ocular tissue in CNV patients. The 1H NMR spectra results revealed successful conjugation of iRGD peptide into PLGA NPs. The miR-539-PLGA.NPs and miR-539-iRGD-PLGA.NPs were prepared and showed a particle size of 300 ± 3 and 306.40 ± 4 nm, respectively. A reduction in human retinal microvascular endothelial cell (HRMEC) viability was shown 48 and 72 h post transfection with miR-539 incorporated in PLGA NPs and iRGD-PLGA.NPs. iRGD-functionalized PLGA NPs caused further significant reduction in cell viability when compared with plain ones, revealing an enhancement in the NP uptake with iRGD-grafted NPs. The current study showed that miR-539-PLGA.NPs and miR-539-iRGD-PLGA.NPs are promising approaches that reduced the viability of HRMECs, suggesting their therapeutic potential in the treatment of CNV.